1998
DOI: 10.1002/pen.10223
|View full text |Cite
|
Sign up to set email alerts
|

A study on the ternary blends of nylon 6, a thermotropic liquid crystalline polymer, and a thermoplastic elastomer

Abstract: Reactive extrusions were performed with blends of nylon 6 and a liquid crystalline copolyesteramide (LCP) including a functionalized elastomer (maleic anhydride grafted ethylene‐propylene‐diene terpolymer). The functionalized elastomer acts as a compatibilizer at the interface. The thermal behavior of the blends suggests partial compatibility of the components endowed by the produced graftcopolymer. A finer dispersion was observed for the compatibilized blends. Fine fibrils were also observed even when no exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 18 publications
0
35
1
Order By: Relevance
“…1, it is readily apparent that the viscosity of the blends decreases with increasing LCP content up to 20 wt.% of LCP, with the further addition of LCP a slight increase in the viscosity of the blends is observed. This decrease in the viscosity at the lower level of LCP were attributed to be formation of the elongated fibrils of the LCP phase, which tend to lubricate the melt [11] . However, at higher levels of LCP the fibrillation capability of LCP diminished, as is revealed by the SEM study.…”
Section: Resultsmentioning
confidence: 98%
“…1, it is readily apparent that the viscosity of the blends decreases with increasing LCP content up to 20 wt.% of LCP, with the further addition of LCP a slight increase in the viscosity of the blends is observed. This decrease in the viscosity at the lower level of LCP were attributed to be formation of the elongated fibrils of the LCP phase, which tend to lubricate the melt [11] . However, at higher levels of LCP the fibrillation capability of LCP diminished, as is revealed by the SEM study.…”
Section: Resultsmentioning
confidence: 98%
“…In the simple shear flow of Newtonian fluids, a dispersed droplets will be elongated if Ca > 0.5, indicating that the ratio of shear stress ( m η γ ) should be larger than a half of the interfacial energy ( / b σ ) (16) .…”
Section: Morphologymentioning
confidence: 99%
“…Machiels et al (12) studied the fiber formation, stability, and properties of TPE (Arnitel EM630)/Vectra A900 blends and reported that the mechanical properties increased with increasing draw ratio of the extrudate as a result of an increase in the fiber aspect ratio and molecular orientation in the TLCP phase. Seo and co-workers (16)- (17) investigated ethylene-propylene-diene monomer rubber (EPDM)/Vectra B950 blends and suggested the effect of elongational deformation on the fibrillation of TLCP. Chakraborty et al (18) studied the self-reinforcing characteristics of Vectra A950 in EPDM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we systematically sought for the preparation method of polyamide in situ composites [14,[23][24][25]. What we found is that an in situ composite of a polyamide can be made even with the extrudates from a twin screw extruder where the shear rate is not high and with very weak or no drawing, provided a compatibilizer is added to the binary blend [23,25].…”
Section: Introductionmentioning
confidence: 99%